Impact of Educational Intervention on the Knowledge of Polycystic Ovarian Syndrome among Lady Health Visitors - Saba Kiran, Rehana Tabbasum, Ayesha Naz, Nadeem Masih, Arfa Nadeem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: PCOS, a common endocrine disorder, is more common in adolescent girls and young women during their reproductive years. According to the World Health Organization (WHO), 116 million (3.4%) of women worldwide have PCOS in 2012. PCOS increases a woman's risk of type 2 diabetes, cardiovascular disease, infertility, anxiety, and depression, as well as a poor quality of life related to her health. Objectives: To determine the impact of education intervention on the knowledge of poly cystic ovarian disease among lady health visitors in Public Health Nursing School Lahore. Methodology: A Quasi- experiment one group pre-test post-test study design was conducted at Public Health Nursing School in Pakistan. A total of 141 people were recruited through random sampling. First- and second-year lady health visitor (LHV) students aged 17 to 30 participated in the study. It was done with full knowledge and consent. To analyze the data, the most recent version of SPSS 24 was employed. Results: According to the study's findings, the bulk of participants, 114 (80.9%), were between the ages of 17 and 20, with 75 (53.2%) of them living in metropolitan regions. The results showed that the data was normally distributed because the P-value was less than 0.05. The findings showed that, in comparison to their values at the pretest, the mean post intervention knowledge score was significantly higher after educational intervention (p 0.0001). Practical Implications: The midwives and labor and delivery nurses (LHVs) play a key role in the healthcare industry. Women should receive counselling, information, and encouragement related to polycystic ovary syndrome. The long-term advantages of education would help women understand how to adjust their lifestyles according to polycystic ovarian syndrome. Conclusion: It is concluded that the post intervention score of participants was high than pre-intervention. As a result, educational sessions had a positive effect on improving knowledge scores about polycystic ovarian syndrome. Keywords: Polycystic Ovarian Syndrome; Knowledge; Educational Intervention; Lady Health Visitor